Protégé-OWL: Creating Ontology-Driven Reasoning Applications with the Web Ontology Language - Rubin, Daniel L. (American Medical Informatics Association, 2005)
Protégé OWL is an open source tool created to support ontology development for the Semantic Web. It is a plug-in extension to the Protégé ontology development platform. Protégé OWL allows users to edit ontologies in the Web Ontology Language (OWL) and to use description logic classifiers to maintain consistency of their ontologies. Protégé OWL can also assist developers of intelligent applications in biomedicine, because many of the problem-solving tasks they seek to automate can be construed as classification tasks. Protégé OWL provides access to emerging knowledge representation standards such as OWL and high-performance classifiers. Being integrated with Protégé, the OWL Plug-in allows users to exploit Protégé’s core features and services such as graphical user interfaces, a variety of storage formats, and data acquisition and visualization tools. Finally, Protégé OWL provides an API allowing it to be integrated into applications.